(3GdWgGQI aj GdCNdGbs - (3CMeO Hf eMeO Hf jYbhH perSncnhrjg, CHh Ydj,J (B421 (3g` s
(3ChdgG (B:s
(3bGd CMeO Hf eMeO eSchQjg ZQVfG ai gPG GdcJGH s
(3BNQgG (B:s
(3aJOGhi faSg efgG hjYGdLgG HebGHdJgG ef GdYdGLGJ hGdQZHI Edi Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B168s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdOcJhQ (B/ (3MSjf Ydi eMahX (B_ (3HZOGO (B(12) s
Keywords: (3GdadSaI hGdefWbs